Acute decompensated heart failure in a non cardiology tertiary referral centre, Sarawak General Hospital (SGH‑HF) - Ling, Hwei Sung; Chung, Bui Khiong; Chua, Pin Fen; Gan, Kai Xin; Ho, Wai Leng; Ong, Elora Yoke Ling; Kueh, Cindy Hui San; Chin, Yie Ping; Fong, Alan Yean Yip (BioMed Central Ltd, 2020)
Abstract Background: Data on clinical characteristics of acute decompensated heart failure (ADHF) in Malaysia especially in East Malaysia is lacking. Methods: This is a prospective observational study in Sarawak General Hospital, Medical Department, from October 2017 to September 2018. Patients with primary admission diagnosis of ADHF were recruited and followed up for 90 days. Data on patient’s characteristics, precipitating factors, medications and short-term clinical outcomes were recorded. Results: Majority of the patients were classified in lower socioeconomic group and the mean age was 59 years old. Hypertension, diabetes mellitus and dyslipidaemia were the common underlying comorbidities. Heart failure with ischemic aetiology was the commonest ADHF admission precipitating factor. 48.6% of patients were having preserved ejection fraction HF and the median NT-ProBNP level was 4230 pg/mL. Prescription rate of the evidencebased heart failure medication was low. The in-patient mortality and the average length of hospital stay were 7.5% and 5 days respectively. 43% of patients required either ICU care or advanced cardiopulmonary support. The 30-day, 90-day mortality and readmission rate were 13.1%, 11.2%, 16.8% and 14% respectively. Conclusion: Comparing with the HF data from West and Asia Pacific, the short-term mortality and readmission rate were high among the ADHF patients in our study cohort. Maladaptation to evidence-based HF prescription and the higher prevalence of cardiovascular risk factors in younger patients were among the possible issues to be addressed to improve the HF outcome in regions with similar socioeconomic background. Keywords: Acute decompensated heart failure, Epidemiology, Sarawak, Southeast Asia, Malaysia